THE EFFECT OF PROBIOTIC ADDITON WITH DIFFERENT DOSE IN FEED TO THE GROWTH OF FISH SILVER POMPANO (Trachinotus blochii, Lacepede) - Delvia Prellia S.; Usman M Tang; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on February 24th up to March 24th 2016 at Balai Perikanan Budidaya Laut Batam. This research aims to understand the effect of adding probiotic and investigate the best dose of probotic for growth of fish silver pompano (Trachinotus blochii, Lacepede). The research method was experimental method and Complete Random Device (CRD) with four treatments and three replications. The treatments in this research was P0= no Probiotic (control); P1= 1.0 g probotic/kg of feed ; P2= 2.0 g Probiotic/Kg of feed and P3= 3.0 g probiotic/kg of feed. To understand the development of the fish, body weight and total length was measured every 10 days. The result shown that the best dose of probiotic was P3 with 3.0 g probiotic/kg of feed which provides absolute growth body weigths (1.01g), growth total length (2.57 cms) and survival rate was (100%). But the best efficiency of feed was in P1 (1g probiotic/kg of feed) namely (95.52%).Key Words : Probiotic, Silver pompano, Growth, Survival